Fractional Calculus Applications in Modeling and Design of Control Systems - Muresan, Cristina I.; Ostalczyk, Piotr; Ortigueira, Manuel D. (Journal of Applied Nonlinear Dynamics, 2026)
Fractional calculus represents the generalization of integration and differentiation to an arbitrary order. Since the very first occurrence of fractional differentiation more than 300 years ago, fractional calculus and research related to its possible application have deserved ever-growing attention and interest. The research community has managed to bring forward ideas and concepts that justify the importance of fractional calculus for future engineering and science discoveries. What has begun as a means to describe abnormal behaviours in viscoelasticity or diffusion, power law phenomena, long range processes or fractal structures has spread to almost all engineering fields and applied sciences. Nowadays, its use in control engineering has been gaining more and more popularity in both modeling and identification, as well as in the controller tuning.